2000
DOI: 10.1523/jneurosci.20-14-05516.2000
|View full text |Cite
|
Sign up to set email alerts
|

Timing Mechanisms in the Cerebellum: Testing Predictions of a Large-Scale Computer Simulation

Abstract: We used large-scale computer simulations of eyelid conditioning to investigate how the cerebellum generates and makes use of temporal information. In the simulations the adaptive timing displayed by conditioned responses is mediated by two factors: (1) different sets of granule cells are active at different times during the conditioned stimulus (CS), and (2) responding is not only amplified at reinforced times but also suppressed at unreinforced times during the CS. These factors predict an unusual pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
295
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 340 publications
(312 citation statements)
references
References 60 publications
16
295
1
Order By: Relevance
“…The main simplification is that a spike occurs when membrane potential exceeds a threshold value, which itself varies according to previous activity to allow for absolute and relative refractory periods. With the exception of a few unknown values, the cellular and synaptic properties were based on published reports (Medina et al, 2000). As reported previously, the results did not depend on the particular values of the small number of free parameters (Medina et al, 2000, their Table 1).…”
Section: Methodsmentioning
confidence: 68%
See 2 more Smart Citations
“…The main simplification is that a spike occurs when membrane potential exceeds a threshold value, which itself varies according to previous activity to allow for absolute and relative refractory periods. With the exception of a few unknown values, the cellular and synaptic properties were based on published reports (Medina et al, 2000). As reported previously, the results did not depend on the particular values of the small number of free parameters (Medina et al, 2000, their Table 1).…”
Section: Methodsmentioning
confidence: 68%
“…This evidence, combined with the well characterized synaptic organization and physiology of the cerebellum (Eccles et al, 1967;Llinas, 1981;Ito, 1984;Voogd and Glickstein, 1998), makes it possible to build large-scale computer simulations of the cerebellum and to test their capacity to display eyelid conditioning. We have shown previously that, by incorporating the evidence for plasticity at two sites (one in the cerebellar cortex and one in the cerebellar interpositus nucleus), these simulations can emulate the acquisition and extinction of conditioned responses (Medina et al, 2000). Here we report that these same simulations also display savings, even after extensive extinction training.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Why would removing GABAergic inhibition impair the production of CRs? One possibility is that CR production normally requires Purkinje cell inhibition to produce a rebound depolarization or to specifically shape CR topography (Aizenman & Linden, 1999;Gould & Steinmetz, 1996;Hesslow, 1994;Katz, Tracy, & Steinmetz, 2001;Medina, Garcia, Nores, Taylor, & Mauk, 2000;Schreurs, 2000;Schreurs et al, 1998). Blocking GABAergic synaptic transmission would block the inhibition that is necessary for producing the rebound response in the interpositus nucleus (Aizenman & Linden, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Early results in rabbits ranged from complete abolition of the learned responses pointing to the cerebellar cortex as the key site (Yeo, 1991) to nominal effects that suggested a more fundamental role for the AIN (McCormick and Thompson, 1984). Numerous subsequent studies measuring closure of the external eyelid or nictitating membrane have reported responses with relatively fixed and short latencies to onset (ϳ80 -150 ms) after direct lesions (McCormick and Thompson, 1984;Perrett et al, 1993;Perrett and Mauk, 1995;Garcia et al, 1999;Medina et al, 2000) or infusing GABA A antagonists into the AIN (Garcia and Mauk, 1998;Medina et al, 2001;Ohyama and Mauk, 2001;Bao et al, 2002;Ohyama et al, 2003;Aksenov et al, 2004). We previously hypothesized that these short-latency responses (SLRs) (see Fig.…”
Section: Introductionmentioning
confidence: 99%